Incarcerated stories: indigenous women migrants and violence in the settler-capitalist state - Speed, Shannon (Critical indigeneities, 2019)
"Incarcerated stories uses ethnography and oral history to document and assess the plight of indigenous women migrants from Mexico and Central America to the United States. Their harrowing experiences of violence before, during, and after their migration parallel the worst stories we hear about immigrants' journeys; but as Speed argues, the circumstances for indigenous women are especially devastating against the backdrop of neoliberal economic and political reforms that have taken hold in Latin America as well as the U.S. First these women were promised greater autonomy and economic opportunity under reforms meant to promote indigenous rights at home, but the attention given to indigenous recognition veiled policies that furthered the economic disruption for women"--